Analisa Usability Website Akademi Komunitas Negeri Pacitan Menggunakan Metode Heuristic Evaluation - Kurnianto Tri Nugroho; Bagus Julianto; Gramandha Wega Intyanto; Mochammad Syahrul Munir; Danny Febryan Nur M.S. (UIN Sunan Kalijaga Yogyakarta, 2020)
The development of information technology today provides many changes to human life, one of which is the website. The website of the university in particular can help the wider community, especially students, in obtaining information. Akademi Komunitas Negeri (AKN) Pacitan is one of the many colleges that utilize information technology in the form of websites. To find out whether the website created has made it easy for users, it is necessary to analyze the usability of the website. This study will analyze the level of usability on the AKN Pacitan website with the Heuristic Evaluation method. The variables used in this study are five usability variables of the ten variables in the Heuristic Evaluation method, including visibility of system status, the match between system and the real world, consistency and standards, flexibility and efficiency of use, and aesthetic and minimalist design. The population of this research is students, lecturers, and AKN Pacitan staff, using probability sampling, simple random sampling, and proportionate stratified random sampling as data collection techniques. The research data was taken using a questionnaire and analyzed using descriptive analysis methods. From the results of the subsequent questionnaire, the analysis will produce several recommendations for improvement and further development of the AKN Pacitan website to improve the functionality of the website itself.